Digital Transformation in Villages: Its Impact On Human Resource Management And Community Empowerment - Pujiyanto, Rahmat; Bratamanggala, Rudi (Pelopor Publikasi Akademika, 2024)
This study aims to explore the influence of digital transformation on human resource (HR) development and community empowerment in villages, as well as to identify the challenges and potentials in the process. Digital transformation is considered one of the innovative strategies to improve the efficiency of village management and strengthen the capacity of communities to actively participate in various development programs. Digitalization can include increasing access to information, transparency of public services, and developing technological skills needed in today's digital era. This study uses a quantitative approach with a survey method involving 300 respondents from several villages that have implemented digital transformation at different scales. The data collection instrument in the form of a questionnaire was tested first to ensure its validity and reliability, which showed that all items had good validity and reliability values. The results of the data analysis revealed that the application of digital technology had a significant impact on community perception and involvement, especially in increasing knowledge and participation in village development programs. The younger generation proved to be more responsive and adaptive to the use of technology compared to the older generation, indicating a gap in technology acceptance between age groups. In addition, the results of the study also showed that increased use of technology was directly proportional to increased community participation in empowerment programs.